PENGARUH PENERAPAN METODE PERMAINAN TRADISIONAL ENGKLEK TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV DI SEKOLAH DASAR - Novriyanti, Nova; Maryamah, Maryamah; Dwi Saputra, Agra; Nurlaila, Nurlaila; Hasmayanti Agustina, Rika; Juabdin Sada, Heru (Limas PGMI, 2024)
The learning methods used in the fourth grade Mathematics learning process at SD Negeri 12 Lahat are less varied, this causes some students to be less enthusiastic about participating in learning activities. The aim of this research is to determine the effect of applying the engklek game method on students' learning motivation in class IV Mathematics learning at SD Negeri 12 Lahat. The type of research used in this research is quantitative. The method used is the True Experimental Design method with a posttest-only control design research design. The sample in this study was class IV B students as an experimental class with a total of 20 students and class IV A as a control class with a total of 18 students. The application of the traditional engklek game method to student learning motivation in mathematics learning is classified as very good. The experimental class obtained an average of 58.75 while the control class obtained an average of 53.67. Thus, the learning motivation category for the experimental class which applied the traditional engklek game method was higher than the control class which did not apply the traditional engklek game method. The results of research and data analysis obtained a significant value, namely 0.002 < 0.05, which means that H0 is rejected and Ha is accepted. From the research results, it can be concluded that there is an influence of the traditional engklek game method on student learning motivation.